The bog wife : a novel - Chronister, Kay (Counterpoint, 2024)
"Since time immemorial, the Haddesley family has tended the cranberry bog. In exchange, the bog sustains them. The staunch seasons of their lives are governed by a strict covenant that is renewed each generation with the ritual sacrifice of their patriarch, and in return, the bog produces a "bog-wife." Brought to life from vegetation, this woman is meant to carry on the family line. But when the bog fails--or refuses--to honor the bargain, the Haddesleys, a group of discordant siblings still grieving the mother who mysteriously disappeared years earlier, face an unknown future. Middle child Wenna, summoned back to the dilapidated family manor just as her marriage is collapsing, believes the Haddesleys must abandon their patrimony. Her siblings are not so easily persuaded. Eldest daughter Eda, de facto head of the household, seeks to salvage the compact by desecrating it. Younger son Percy retreats into the wilderness in a dangerous bid to summon his own bog-wife. And as youngest daughter Nora takes desperate measures to keep her warring siblings together, fledgling patriarch Charlie uncovers a disturbing secret that casts doubt over everything the family has ever believed about itself"--